2007
DOI: 10.1097/brs.0b013e3180bc225d
|View full text |Cite
|
Sign up to set email alerts
|

Horner Syndrome due to a Solitary Osteochondroma of C7

Abstract: Vertebral involvement of osteochondroma is rare, especially with neurologic compromise. A young patient is presented with a symptomatic solitary osteochondroma of the seventh cervical vertebra who had Horner syndrome. This case report supports surgical intervention of symptomatic osteochondroma of the cervical spine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 16 publications
0
9
0
Order By: Relevance
“…10 Spinal involvement is rare. [11][12][13] Only 1.3-4.1% of solitary osteochondromas arise in the spine, 14 where they constitute up to 0.4% of intraspinal tumors or 3.9% of solitary spinal tumors. 5 Unlike pedunculated long bone osteochondromas, vertebral osteochondromas are sessile.…”
Section: Discussionmentioning
confidence: 99%
“…10 Spinal involvement is rare. [11][12][13] Only 1.3-4.1% of solitary osteochondromas arise in the spine, 14 where they constitute up to 0.4% of intraspinal tumors or 3.9% of solitary spinal tumors. 5 Unlike pedunculated long bone osteochondromas, vertebral osteochondromas are sessile.…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of neurological symptoms including myelopathy and radiculopathy caused by the tumor was 0.5–1 % (Brastianos et al 2005 ; Ratliff and Voorhies 2000 ). Rare osteochondroma arising anteriorly from the cervical vertebral body can compress the surrounding tissues, and cause dysphagia (Grivas et al 2005 ; Wong et al 2013 ), sleep apnea (Wang and Chou 2009 ), respiratory distress, vocal cord paralysis (Certo et al 2014 ), and Horner syndrome (Zhao et al 2007 ). Moreover, Certo et al ( 2014 ) reported the correlation between tumor development and presence of diffuse idiopathic skeletal hyperostosis.…”
Section: Discussionmentioning
confidence: 99%
“… 4 The patient reported here was in her fifth decade of life (42 years of age), an age group in which only 5% of the diagnoses are made. 5 …”
Section: Discussionmentioning
confidence: 99%
“…Occurrences in the ischium are uncommon and account for 0.4% of the cases. 5 They can be solitary or multiple. The latter are associated with multiple hereditary exostosis, which is an autosomal dominant syndrome.…”
Section: Discussionmentioning
confidence: 99%